Mengeksplorasi keanekaragaman hayati, lingkungan dan pandangan masyarakat lokal mengenai berbagai lanskap hutan: metode-metode penilaian lanskap secara multidisipliner - Sheil, Douglas; Puri, R.K.; Basuki, I.; Heist, M. van; Wan, M.; Liswanti, N.; Rukmiyati; Sardjono, M.A.; Samsoedin, I.; Sidiyasa, K.D.; Chrisandini; Permana, E.; et al. (Center for International Forestry Research, 2004)
This document is intended for those interested in gathering natural resource information that reflects the needs of local communities. It describes a multidisciplinary survey developed with indigenous communities in the fores-rich landscapes of the Malinau watershed in East Kalimantan (Indonesian Borneo). The final methods reflect a mixture of judgements, compromises and reactions to trials over many months. It is intended that it is useful to readers from diverse backgrounds given the multidisciplinary nature of the procedures described. This is not intended as a manual. It is a summary of lessons learned.